BEBERAPA KOMBINASI RUNGE-KUTTA UNTUK MENENTUKAN SOLUSI PERSAMAAN DIFERENSIAL WAKTU TUNDA - Qudsi Rahma; Agus Dahlia (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2019)
Delay Differential Equation (DDE) have been applied to many area. While, we rarely get the analytic solutions of DDE. Many researchers have found many methods to find it for instance Runge-Kutta Method. The purpose of this paper is to accumulate the combinations of Runge-Kutta method which is used to find the solutions of DDE.